Vitamin D: a negative acute phase reactant. Issue 7 (1st March 2013) - Waldron, Jenna Louise; Ashby, Helen L; Cornes, Michael P; Bechervaise, Julia; Razavi, Cyrus; Thomas, Osmond L; Chugh, Sanjiv; Deshpande, Shreeram; Ford, Clare; Gama, Rousseau
Abstract : Objective: We evaluated the effect of the systemic inflammatory response (SIR), as provoked by elective orthopaedic surgery, on serum vitamin D [25-(OH)D]. Methods: Serum 25-(OH)D, serum vitamin D binding protein (VDBP) and urinary VDBP were measured in 30 patients before and 48-hours after knee or hip arthroplasty. C-reactive protein (CRP) was measured to assess the SIR. Results: The mean (SD) CRP increased following surgery [5.0 (5.5) vs 116.0 (81.2) mg/L; P<0.0001] as did urine VDBP/Creatinine ratio [8 (9) vs 20 (25) pg/mmol; p=0.0004]. Serum 25-(OH)D [56.2 (30.3) vs 46.0 (27.6) nmol/L; p = 0.0006] and serum VDBP [334 (43) vs 298 (37) mg/L]; P<0.0001] decreased. Conclusions: Serum 25-(OH)D is a negative acute phase reactant, which has implications for acute and chronic inflammatory diseases. Serum 25-(OH)D is an unreliable biomarker of vitamin D status after acute inflammatory insult. Hypovitaminosis D may be the consequence rather than cause of chronic inflammatory diseases.